(untitled) (Revista LIDER, 2020)
The study about contemporary Mapuche population implies recognizing the existence of a complex spatial and socioeconomic mobility constituted from a process shaped, at least, by two moments: (1) migrating population from the towns of the south of the country, and (2) trying to be a part of the big cities, specially in Santiago, the capital. Therefore, in this text it is sought to answer to the questions: which are the reasons that lead to an important part of the Mapuche population to leave their origin places? And which are the conditions that facilitate or impede the integration of the Mapuche immigrants in the Metropolitan Region? Then, the historical mapuche impoverishment is analyzed in the rural localities, as well as the social networks and the ethnic empowerment that has been forged during the last decades from the urban spaces (labor and neighborhood) of ethnic